Fra renegat til arbejderhelt. Poul Geleffs amerikanske eksil og hjemkomst til Danmark, 1876-1928 - Larsen, Tina Langholm (Historisk Tidsskrift, 2025)
For more than a century, Poul Johansen Geleff (1842-1928) has been celebrated in Social Democratic historiography as a pioneer of Danish Socialism alongside Louis Pio and Harald Brix. However, this article reminds us that the narrative surrounding him has evolved significantly. Geleff and Pio had been portrayed as traitorous exiles in the late nineteenth century, but were rehabilitated in connection with the 1921 celebrations of the Social Democratic Party’s 50th anniversary. Drawing on archival material from Denmark and the United States, the article explores Geleff’s American exile (1877-1920), his ideological stance, and the sociopolitical factors prompting his return. The analysis draws on memory studies, particularly the construction of collective memory as a power mechanism to solidify political identity and shape national narratives. Situating Geleff’s story within broader Scandinavian research on transatlantic exchanges and their influence on labour movements and democratic development, the article also contributes to the history of the Social Democratic Party, the Danish labour movement, and Danish American migration.